Bleeding and safety outcomes in persons with haemophilia A without inhibitors: Results from a prospective non‐interventional study in a real‐world setting. Issue 2 (6th February 2019) - Kruse‐Jarres, Rebecca; Oldenburg, Johannes; Santagostino, Elena; Shima, Midori; Kempton, Christine L.; Kessler, Craig M.; Lehle, Michaela; Chebon, Sammy; Selak Bienz, Nives; Asikanius, Elina; Mahlangu, Johnny
Abstract : Introduction: Prospectively collected real‐world data on bleeds, haemophilia treatment and safety in persons with haemophilia A (PwHA) without factor VIII (FVIII) inhibitors are limited. A global, non‐interventional study (NIS; NCT02476942) prospectively collected real‐world data in PwHA who were treated per local routine clinical practice. Aim: Assess annualized bleeding rate (ABR), haemophilia treatment practices and adverse events (AEs) in adult/adolescent PwHA without inhibitors. Methods: Eligible participants aged ≥12 years with severe HA without history of inhibitors prospectively collected bleeding and treatment information. Results: Ninety‐four participants were enrolled (median [range] age, 34 [12‐76] years) and monitored for a median (range) of 29.8 (12.4‐47.7) weeks. In the episodic (n = 45) and prophylactic (n = 49) treatment groups, respectively, 872/1066 (81.8%) and 151/189 (79.9%), bleeds were treated; ABRs (95% confidence interval) were 36.1 (30.8‐42.3) and 5.0 (3.3‐7.5), respectively, for treated bleeds and 43.1 (36.5‐50.9) and 6.2 (4.2‐9.2), respectively, for all bleeds, and median (interquartile range) ABRs were 31.1 (19.8‐51.6) and 1.9 (0.0‐8.2), respectively, for treated bleeds and 35.3 (21.7‐62.9) and 2.7 (0.0‐9.4), respectively, for all bleeds. Half of the participants on FVIII prophylaxis had relatively high adherence to treatment, using 2.9 and 2.1 median doses/wk of standard and extended half‐life FVIII, respectively. Serious AEs included gastrointestinal polyp haemorrhage and haemarthrosis; the most common AE was viral upper respiratory tract infection. Conclusion: PwHA without inhibitors continue to bleed on prophylaxis, consistent with the literature, and require treatment for breakthrough bleeds. This prospective NIS demonstrates the need for more efficacious haemostatic approaches.